2003
DOI: 10.1016/s1074-5521(03)00147-9
|View full text |Cite
|
Sign up to set email alerts
|

Preferred RNA Binding Sites for a Threading Intercalator Revealed by In Vitro Evolution

Abstract: In pursuit of small molecules capable of controlling the function of RNA targets, we have explored the RNA binding properties of peptide-acridine conjugates (PACs). In vitro evolution (SELEX) was used to isolate RNAs capable of binding the PAC Ser-Val-Acr-Arg, where Acr is an acridine amino acid. The PAC binds RNA aptamers selectively and with a high degree of discrimination over DNA. PAC binding sites contain the base-paired 5'-CpG-3' sequence, a known acridine intercalation site. However, RNA structure flank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 68 publications
0
63
0
Order By: Relevance
“…[12,13] Using these criteria, we identified a sequence within helix 22 of E. coli 16S RNA as a possible target. Interestingly, this notion was supported by the work of Kean et al in which it was demonstrated that the classical intercalator ethidium bromide bound selectively to this site.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[12,13] Using these criteria, we identified a sequence within helix 22 of E. coli 16S RNA as a possible target. Interestingly, this notion was supported by the work of Kean et al in which it was demonstrated that the classical intercalator ethidium bromide bound selectively to this site.…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15] Early studies by Cech and Draper, as well as more recent efforts by us and others, have established that certain duplex-RNA structures are predisposed to high-affinity intercalation and can be selectively targeted by intercalating ligands. [12,13,[15][16][17][18][19][20][21] Therefore, one approach to generating a highly selective RNA-binding compound is through modification of an intercalating ligand to maximize binding at one of these high-affinity sites, while minimizing nonselective binding to other double-helical structures. In duplex RNA, the major and minor grooves contain functional groups that provide unique recognition surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately at this time, there is no clear pattern of molecular structures that favor RNA over DNA interactions among intercalators [40,41], although threading intercalators can bind to certain sites on RNA with higher affinity than to B-form DNA duplexes [37].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, quinacrine showed no effect on firefly or renilla production at 10 lM final concentration. A number of peptide-acridine conjugates (PAC) have been described as novel RNA-binding ligands [36,37]. 9-Anilinoacridine-4-carboxamides can act as threading intercalators, wherein the core acridine moiety stacks between base-pairs and directs its substituents into both grooves of the RNA duplex [22,23].…”
Section: Structure Activity Relationships Analysis Of Acridine Basedmentioning
confidence: 99%
“…[5] Peptide functional groups attached to the heterocycle extend into the dissimilar RNA duplex grooves. [6] The peptide appendages provide stabilizing interactions in the grooves of the target RNA.…”
mentioning
confidence: 99%